The chaotic city: ideology and crise’s simulation in urban society - Barbosa, Jorge Luiz (GEOUSP Espaço e Tempo (Online), 2001)
This article objectes to develop a critical reflexion on the present changes in society and its implications in the making of urban landscape. We search the possible ways in understanding the contemporany transformation in the urban space and the representations of the chaos in wich is explicit the big "shopping center" the city visual became